O-GlcNAc cycling enzymes control vascular development of the placenta by modulating the levels of HIF-1α. Issue 10 (October 2015) - Yang, Yong Ryoul; Jang, Hyun-Jun; Lee, Yong Hwa; Kim, Il Shin; Lee, Ho; Ryu, Sung Ho; Suh, Pann-Ghill
Abstract Introduction Placental vasculogenesis is essential for fetal growth and development, and is affected profoundly by oxygen tension (hypoxia). Hypoxia-inducible factor-1α (HIF-1α), which is stabilized at the protein level in response to hypoxia, is essential for vascular morphogenesis in the placenta. Many studies suggested that responses to hypoxia is influenced by O-GlcNAcylation. O-GlcNAcylation is regulated by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA) that catalyze the addition and removal of O-GlcNAc respectively. Methods We generated OGA deficient mice and evaluated OGA−/− placentas. The analysis of OGA−/− placentas was focused on morphological change and placental vasculogenesis. HIF-1α protein stability or transcriptional activity under dysregulation of O-GlcNAcylation were evaluated by Western blot, RT-qPCR and luciferase reporter gene assays in MEFs or MS1 cell line. Results Deletion of OGA results in defective placental vasculogenesis. OGA−/− placentas showed an abnormal placental shape and reduced vasculature in the labyrinth, which caused a developmental delay in the embryos. OGA deletion, which elevates O-GlcNAcylation and downregulates O-GlcNAc transferase (OGT), suppressed HIF-1α stabilization and the transcription of its target genes. In contrast, the overexpression of O-GlcNAc cycling enzymes enhanced the expression and transcriptional activity of HIF-1α. Discussion These results suggest that OGA plays a critical role in placental vasculogenesis by modulating HIF-1α stabilization. Control of O-GlcNAcylation is essential for placental development.